Green Betel Leaf Water with Pure Honey Against Healing Perineum's Wounds Mother Postpartum - Dompas, Robin; Montolalu, Agnes; Koloay, Trifena Gabriely (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2022)
Many postpartum mothers die from perineal injuries. Perineal infection can occur if the perineal wound is not treated correctly and correctly. This study was conducted to assess the effectiveness of healing wounds perineum postpartum mothers using green betel leaves and pure honey. This type of research is pre-experimental using one pretest group-posttest design. The number of 20 samples is determined by purposive sampling. Intervention is done using betel leaf decoction water to rinse perineal wounds for one week. Water is made from 5 sheets of betel leaves boiled with 1000 millilitres of water for 30 minutes to 600 millilitres. Data collection uses observation sheets filled in before and after the intervention. Analysis of data using the McNemar test obtained the result of the P-value 0.021 with the meaning <0.05. The results showed an effect of giving green betel leaf water and consuming pure honey to heal perineal wounds in postpartum mothers, so it is recommended that postpartum mothers suffering from perineal wounds use a decoction of green betel leaf water to rinse the perineum and consumption. Pure honey because of the benefits and content obtained in green betel leaves and pure honey in healing perineal wounds.